Metabolite Profiling of Paraquat Tolerant Arabidopsis thaliana Radical-induced Cell Death1 (rcd1)-A Mediator of Antioxidant Defence Mechanisms - Nina Sipari; Jenna Lihavainen; Markku Keinänen (MDPI AG, 2022)
RADICAL-INDUCED CELL DEATH1 (RCD1) is an Arabidopsis thaliana nuclear protein that is disrupted during oxidative stress. RCD1 is considered an important integrative node in development and stress responses, and the rcd1 plants have several phenotypes and altered resistance to a variety of abiotic and biotic stresses. One of the phenotypes of rcd1 is resistance to the herbicide paraquat, but the mechanisms behind it are unknown. Paraquat causes a rapid burst of reactive oxygen species (ROS) initially in the chloroplast. We performed multi-platform metabolomic analyses in wild type Col-0 and paraquat resistant rcd1 plants to identify pathways conveying resistance and the function of RCD1 in this respect. Wild type and rcd1 plants were clearly distinguished by their abundance of antioxidants and specialized metabolites and their responses to paraquat. The lack of response in rcd1 suggested constitutively active defense against ROS via elevated flavonoid, glutathione, β-carotene, and tocopherol levels, whereas its ascorbic acid levels were compromised under non-stressed control conditions when compared to Col-0. We propose that RCD1 acts as a hub that maintains basal antioxidant system, and its inactivation induces defense responses by enhancing the biosynthesis and redox cycling of low molecular weight antioxidants and specialized metabolites with profound antioxidant activities alleviating oxidative stress.